Analisis Implementasi Sistem Informasi Arsip Pada Kantor Pusat PT Perkebunan Nusantara III Medan - sabila devia miranti (Jurnal Pustaka Nusantara dan Budaya, 2013)
This research are purposed to analyze archive information system on the headquarter of PTPN III. The analysis included the implementation of using application software and ongoing process mechanism in managing of in-active archive. The methods in this research was using descriptive research and qualitative approaching. The determination of the informant was done  by purposive sampling method. Data was collected by using observation on archival unit of work and deep interview to executive employees of archives. The analysis was done by grouping the data of the result of the interview and observation based on two stages, identification of problems and analysis of the need of information system and system recommendation. The result of this research indicated that the process mechanism of implementation of archival information system was not working properly due to less of supportive application in managing the active and in-active archives as well as the lack off knowledge of the employees about the importance of the archive for an institution and caused the load of work has not finished on time. The research was analyzing the need of archival information system and also to increase the knowledge an input about managing the archives properly. Based on the result of need the system, we need the new archival application system which is integrated and capable to manage the active and in-active archives in order to smooth the process of managing the archives on the PTPN III headquarter, also to socialize the employees about archival in order to complete the load of work on time.